APPROPRIATE MODELS FOR MEASURING INTANGIBLE ASSETS AND THEIR IMPACT ON THE FINANCIAL STATEMENTS AND MANAGEMENT DECISIONS: AN APPLIED STUDY IN AL-MANSOUR PHARMACEUTICAL INDUSTRIES - Ahmed Rahi Abed; Shaymaa Abdulhusein Abdulkadhim Alisawi; Alaa Miran Hussein (Journals Park Publishing, 2023)
The research aims to focus on two important aspects, namely measuring intangible assets and showing their impact on the financial statements and management decisions. The objectives of the research can be clarified by presenting and discussing the concept of intangible assets and methods of measuring them, presenting and discussing the concept of financial statements and management decisions, and indicating the extent of interest of listed Iraqi companies. In the Iraq Stock Exchange by measuring the intangible assets, in addition to measuring the value of the intangible assets of the Iraqi companies listed in the Iraq Stock Exchange. The research was applied in Al-Mansour Pharmaceutical Industries Company for the period (2016-2020). The research reached a set of conclusions, the most important of which was that (Tobin's Q) model is one of the best models for measuring intangible assets because this model moves away from diligence and personal appreciation, in addition to that this model enhances the principle of comprehensive disclosure, as the current financial disclosure process neglects disclosure For internally formed intangible assets that constitute a large part of the company's assets.